2020
DOI: 10.14814/phy2.14532
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive and innate immune mechanisms in cardiac fibrosis complicating pulmonary arterial hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a syndrome diagnosed by increased mean pulmonary artery (PA) pressure and resistance and normal pulmonary capillary wedge pressure. PAH is characterized pathologically by distal pulmonary artery remodeling, increased pulmonary vascular resistance, and plexiform lesions (PLs). Right ventricular fibrosis and hypertrophy, leading to right ventricular failure, are the main determinants of mortality in PAH. Recent work suggests that right ventricular fibrosis results from re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 113 publications
0
5
0
Order By: Relevance
“…As for PHA-related research fields, it has been reported that caspase-1 can regulate inflammatory factors and participate in the occurrence and development of PHA [ 28 ]. IL-1 can mediate the recruitment of macrophages around pulmonary vessels in mice, promote the abnormal proliferation of PASMCs, and cause pulmonary vascular remodeling, which is closely related to the disease progression of PHA [ 29 , 30 ]. Curcumin could inhibit the secretion of IL-1 by inhibiting NLRP3 inflammasome, thus playing an anti-inflammatory role.…”
Section: Discussionmentioning
confidence: 99%
“…As for PHA-related research fields, it has been reported that caspase-1 can regulate inflammatory factors and participate in the occurrence and development of PHA [ 28 ]. IL-1 can mediate the recruitment of macrophages around pulmonary vessels in mice, promote the abnormal proliferation of PASMCs, and cause pulmonary vascular remodeling, which is closely related to the disease progression of PHA [ 29 , 30 ]. Curcumin could inhibit the secretion of IL-1 by inhibiting NLRP3 inflammasome, thus playing an anti-inflammatory role.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary artery remodeling is known to be associated with increased pulmonary vascular resistance, which can lead to cardiac fibrosis (Siamwala et al, 2020); this could explain the cardiac interstitial fibrosis detected in the heart of the cases examined.…”
Section: Discussionmentioning
confidence: 95%
“…A large proportion of the CD45+ hematopoietic cells appeared to be neither T cells, B cells nor DCs, but might be macrophages or monocytes, since these cells comprise a large population in the heart, both in health and disease (reviewed in [ 34 , 35 ]). Macrophages are implicated in PAH [ 25 , 28 ], possibly by inflammasome-dependent secretion of pro-inflammatory cytokines such as IL-1β and IL-18 [ 36 , 37 ], which are increased in serum of PAH patients [ 15 ]. Interestingly, it has been found in mice that A20-deficient macrophages show spontaneous inflammasome activity and IL-1β secretion [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%